2015
DOI: 10.1371/journal.pone.0122942
|View full text |Cite
|
Sign up to set email alerts
|

RTA 408, A Novel Synthetic Triterpenoid with Broad Anticancer and Anti-Inflammatory Activity

Abstract: Semi-synthetic triterpenoids are antioxidant inflammation modulator (AIM) compounds that inhibit tumor cell growth and metastasis. Compounds in the AIM class bind to Keap1 and attenuate Nrf2 degradation. In the nucleus, Nrf2 increases antioxidant gene expression and reduces pro-inflammatory gene expression. By increasing Nrf2 activity, AIMs reduce reactive oxygen species and inflammation in the tumor microenvironment, which reverses tumor-mediated immune evasion and inhibits tumor growth and metastasis. AIMs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 52 publications
4
70
0
Order By: Relevance
“…Unfortunately, the trial was stopped in 2012 due to a higher rate of cardiovascular events observed in the bardoxolone methyl group compared to placebo [208]. A new CDDO derivative (RTA 408) is already developed and being tested in clinical trials for a variety of non-neurodegenerative diseases, [209212]. More recently, a clinical trial using RTA 408 was initiated for Friedreich's ataxia, a neurodegenerative condition responsible for cerebellar ataxia due to impaired production of the protein frataxin leading to profound deficiencies in mitochondrial respiration (ClinicalTrials.gov Identifier NCT02255435).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the trial was stopped in 2012 due to a higher rate of cardiovascular events observed in the bardoxolone methyl group compared to placebo [208]. A new CDDO derivative (RTA 408) is already developed and being tested in clinical trials for a variety of non-neurodegenerative diseases, [209212]. More recently, a clinical trial using RTA 408 was initiated for Friedreich's ataxia, a neurodegenerative condition responsible for cerebellar ataxia due to impaired production of the protein frataxin leading to profound deficiencies in mitochondrial respiration (ClinicalTrials.gov Identifier NCT02255435).…”
Section: Discussionmentioning
confidence: 99%
“…Its oral formulation BG-12 has been recently approved for the treatment of multiple sclerosis (Linker et al, 2011). Other molecules able to stabilize Nrf2 are the quinone compound tert-butylhydroquinone (tBHQ) (Li et al, 2005) and the triterpenoids bardoxolone methyl (Dinkova-Kostova et al, 2005) and RTA 408 (Probst et al, 2015), both of which are currently in clinical trials.…”
Section: Nrf2 Activatorsmentioning
confidence: 99%
“…The mechanism of action of bardoxolone consists of causing a reversible Michael addition of SH groups in Keap‐1 to attenuate Nrf2 degradation; as mentioned earlier, this is one of the main defence systems against redox stress. Some compounds, such as RTA 408, a novel synthetic triterpenoid related to bardoxolone, are cytotoxic in cancer cells by this mechanism (Probst et al ., ). It is therefore postulated that some of these compounds could act as ‘chemical irritants’ to activate body defences.…”
Section: Nrf2‐mediated Antioxidant Action As a Therapeutic Target In mentioning
confidence: 99%